2020
DOI: 10.1515/openec-2020-0002
|View full text |Cite
|
Sign up to set email alerts
|

Multi-faceted insights of entrepreneurship facing a fast-growing economy: A literature review

Abstract: This study explores entrepreneurship research in Vietnam, a lower-middle-income country in Southeast Asia that has witnessed rapid economic growth since the 1990s but has nonetheless been absent in the relevant Western-centric literature. Using an exclusively developed software, the study presents a structured dataset on entrepreneurship research in Vietnam from 2008 to 2018, highlighting: low research output, low creativity level, inattention to entrepreneurship theories, and instead, a focus on practical bus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 92 publications
(70 reference statements)
0
7
0
Order By: Relevance
“…This open database quantifies and records data on research in the social science and humanities from 2008 onward. Such efforts have to be fruitful with foundational works in 2017 and early 2018 (Ho et al 2017a , b ; Vuong et al 2018 ), a data article in 2018 (Vuong et al 2018 ), in-depth analysis of entrepreneurship research (Vuong et al 2020b , d ), and investigations of international publishing in Vietnam from various perspectives (Vuong et al 2020a , c , e ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…This open database quantifies and records data on research in the social science and humanities from 2008 onward. Such efforts have to be fruitful with foundational works in 2017 and early 2018 (Ho et al 2017a , b ; Vuong et al 2018 ), a data article in 2018 (Vuong et al 2018 ), in-depth analysis of entrepreneurship research (Vuong et al 2020b , d ), and investigations of international publishing in Vietnam from various perspectives (Vuong et al 2020a , c , e ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study found that researchers at universities had higher productivity than researchers based at research institutions. In other publications, a dataset of 111 articles in the entrepreneurship research was extracted from the SSHPA for a thorough investigation of the discipline (Vuong et al 2020b , d ). Vuong et al ( 2020b ) suggested a focus on the management side of entrepreneurship, the topics of innovation and creativity or culture are still unexplored territory.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Vuong et al (2020d) suggested a focus on the management side of entrepreneurship, the topics of innovation and creativity or culture is still unexplored territory. Vuong et al (2020f) founded that Vietnamese entrepreneurship researchers still focus on practical issues rather than entrepreneurship theories. The most recent works suggested that more Vietnamese authors have been taking the leading role, and there is a shift from international collaboration to domestic collaboration .…”
Section: Scientific Research In Vietnammentioning
confidence: 99%
“…The results are presented in Table 1. [15] Explaining micro entrepreneurship in rural Vietnam-a multilevel analysis 2018 20 [16] Entrepreneurship and creativity in transition turmoil: the case of Vietnam 2013 14 [17] Previous studies suggested there are not many papers on Vietnam's entrepreneurship [18,19]. However, the fields have started to attract more attention because of the stable development of Vietnam [20].…”
mentioning
confidence: 99%